MARCAN USAGE: NOTES, CRITICAL AND EXE-GETICAL, ON THE SECOND GOSPEL - Turner, C. H. (The journal of theological studies, 1928)
C. H. TURNER; MARCAN USAGE: NOTES, CRITICAL AND EXE-GETICAL, ON THE SECOND GOSPEL, The Journal of Theological Studies, Volume os-XXIX, Issue 115, 1 April 1928,